Politics across the Hudson : the Tappan Zee megaproject - Plotch, Philip Mark, 1961- (New Brunswick, New Jersey : Rutgers University Press, 2018)
Politics Across the Hudson offers a behind-the-scenes look at three decades of contentious planning for the new Tappan Zee Bridge, and includes a new epilogue and more photos, revealing valuable lessons for those trying to tackle complex public policies. Drawing on his own extensive experience in planning megaprojects, more than one hundred exclusive interviews with key figures (including three governors), and extensive research into government records, Philip Plotch tells the compelling, behind-the-scenes story of high-stakes battles between powerful players in the public, private, and civic.
9. David Paterson: The Overwhelmed Governor (2008 -- 2010)10. Andrew Cuomo Takes Charge in 2011; 11. Public Reaction and Cuomo's Campaign (2011 -- 2012); 12. Lost Opportunities and Wasted Resources; Conclusion; Epilogue; Notes; Bibliography; Index; About the Author
Online resource; title from PDF title page (EBSCO, viewed May 14, 2018).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Tappan Zee Bridge (N.Y.); Transportation -- Political aspects -- New York Metropolitan Area; Local transit -- Political aspects -- New York Metropolitan Area; Transportation and state -- New York Metropolitan Area; Transports publics -- Aspect politique -- New York, Agglomération de; Transport -- Politique gouvernementale -- New York, Agglomération de; Transport -- Aspect politique -- New York, Agglomération de; BUSINESS & ECONOMICS -- Industries -- Transportation; TRANSPORTATION -- Public Transportation; Local transit -- Political aspects; Transportation and state; New York (State) -- New York Metropolitan Area; New York (State) -- Tappan Zee Bridge; Electronic books